The importance of relational support for attachment and exploration needs. (February 2019) - Feeney, Brooke C; Collins, Nancy L
Highlights: We review attachment theory postulates related to relational support. We review a perspective on thriving that builds on attachment theory. We emphasize two major functions of support in two life contexts. These support functions promote thriving through adversity and thriving through exploration and growth. We review research on the importance of relational support in each life context. Abstract : In this article, we discuss theory and research on social support and caregiving processes in adult close relationships. We first outline key theoretical principles of attachment theory and of a theoretical perspective on thriving through relationships that builds on attachment theory. We then review empirical research that has tested key theoretical postulates regarding the importance of relational support for both attachment and exploration needs. The empirical review is divided into two components that reflect the two major functions of support/caregiving in close relationships, and that reflect the two different life contexts in which relational support/care is crucial (support in adversity and support for exploration and pursuit of opportunities). We conclude by emphasizing important directions for future research.